RETHINKING HOMO AFRICANUS IN THE CONTEXT OF SOCIO-POLITICAL CHANGE: - A.R. Brunsdon (Acta Theologica)
The article grapples with an appropriate African pastoral anthropology against the background of the socio-political changes that occurred in South of Africa since the dawn of the new democracy during the mid-nineties. It argues that together with the ever-growing process of globalisation, the way that Africans, think, live and believe did not remain untouched. Consequently, pastoral caregivers must question the traditional or romantic view of African believers that still forms the anthropological premise in many pastoral theories. In the light of this, it identifies some of the major socio-political changes that took place in the South African context, which exerted influence on the identity of Africans. It suggests that Africans find themselves amid a realisation of disappointment, loss, anger and feelings of despair. Current day Homo africanus hence calls for a pastoral care of hope to better meet the spiritual needs of African believers, against the background of socio-political change.